2018
DOI: 10.1063/1.5038954
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of surface states hidden in the third layer of Si (111)-7 × 7 surface by pz-wave tip

Abstract: The direct visualization of the surface states of dimers in Si (111)-7 × 7 is still challenging although the DAS model has been proposed 33 years ago. In this letter, based on the partial density of states of the atoms in the reconstructed layers examined by the first principles calculations, scanning tunneling spectroscopy images with a pz-wave tip were carried out, which show a skull pattern at ∼0.7 eV, and 9 bright short lines at ∼1.00 eV in each unit cell, exhibiting obviously the electronic states from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…This energy scale is critical for the Si(111)-7×7 surface and makes different datasets compatible with a metallic 16,18,20 or insulating 17 ground state. Low-temperature STS data 21,22,31,32,47 show the opening of a hard or soft gap below 20 K. However, the published STS spectra are integrated over the unit cell, or taken only on some kinds of the adatoms, or not suitably corrected for the systematic error caused by the non-equilibrium transport of carriers, which affects the energy scale at low temperatures 21,31 . Hence, these analyses do not allow us to identify the adatom-dependent effects of a gap opening at E F .…”
Section: Introductionmentioning
confidence: 99%
“…This energy scale is critical for the Si(111)-7×7 surface and makes different datasets compatible with a metallic 16,18,20 or insulating 17 ground state. Low-temperature STS data 21,22,31,32,47 show the opening of a hard or soft gap below 20 K. However, the published STS spectra are integrated over the unit cell, or taken only on some kinds of the adatoms, or not suitably corrected for the systematic error caused by the non-equilibrium transport of carriers, which affects the energy scale at low temperatures 21,31 . Hence, these analyses do not allow us to identify the adatom-dependent effects of a gap opening at E F .…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Wang et al studied the 7 × 7 from heavily boron‐doped (0.01 Ω cm) sample at 78 K and found that Si‐decorated tips resolved more features in the 7 × 7 images than Pt–Ir tips. [ 37 ] This followed the observations in 1986 that W tips that impacted the surfaces produced higher corrugations and sharper images which was exploited to obtain stable high‐resolution tips to study Si surfaces. [ 106 ] Both work attributed the higher resolution to having a Si atom(s) on the tip with its p z orbital.…”
Section: Analysis and Further Discussionmentioning
confidence: 64%
“…[13] Spin-restricted calculations for possible magnetic surface states were also performed. As in all DFT calculations, the DAS AA bands are partially filled and produce a metallic ground state [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] which is contrary to current experimental measurements showing an energy gap at E F [13,94,99,100] While most of the occupied AA DOS show relatively narrow features, characteristic of localized states, an AA band occurs on the corner AA, as shown in Figure 4b, as low as À0.2 or À0.25 eV for a spin-unrestricted ferromagnetic configuration. [13] Such a ferromagnetic band as calculated is too close to E F to account for the state at %0.5 eV shown in Figure 3a but becomes a possibility as X-C corrections are considered.…”
Section: The Aa Band Tail and The Fssmentioning
confidence: 99%
See 1 more Smart Citation
“…Supervised learning has been applied to SPM in a recent study 22 where ML assists a human operator in detecting and repairing a specific type of probe defect in the particular case of hydrogen-terminated silicon. In this work, a trained CNN assessed the quality of acquired SPM images; if necessary, a wellestablished probe-conditioning protocol was executed 23 . In another recent study 24 , ML was successfully used to determine imaging quality directly from a small number of acquired scan lines, without requiring complete images.…”
mentioning
confidence: 99%